2021
DOI: 10.1097/sle.0000000000000941
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted Treatment of Epigastric Hernias With a Suprapubic Approach

Abstract: Background: Robot-assisted ventral hernia repair has shown itself to be feasible and safe in abdominal wall surgery. Presently, the ports are placed laterally to meet the distance from the fascial defect. The aim of our study is to report our experience of epigastric hernia treatment with trocar insertion in the suprapubic region.Materials and Methods: On a prospectively collected dataset on robot-assisted surgery, patients treated for epigastric hernias with suprapubic approach were identified. Demographic an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Since its introduction into practice, robotic surgery has been applied across a broad range of elective surgical procedures. 8,10 However, robotic-assisted surgery in emergency setting has not been routinely performed and remains, to date, poorly investigated. 4,15 In a recent review, de'Angelis et al found 10 studies (5 cohort studies, 5 case reports) investigating the use of robot-assisted surgery in emergency general surgery.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since its introduction into practice, robotic surgery has been applied across a broad range of elective surgical procedures. 8,10 However, robotic-assisted surgery in emergency setting has not been routinely performed and remains, to date, poorly investigated. 4,15 In a recent review, de'Angelis et al found 10 studies (5 cohort studies, 5 case reports) investigating the use of robot-assisted surgery in emergency general surgery.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous study of ours, an experienced laparoscopic general surgeon requires about 43 R-TAPP to achieve the learning curve. 8 Our robotic operative room is equipped with the Da Vinci Xi dual console, which enables teaching in a quiet and efficient environment and gradually exposes trainees with different level of competence to robotic surgery. 15 Our surgical team undergoes ongoing training aimed at refining their proficiency in utilizing this technology, applicable not only to elective cases but also emergent scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations